The development of the husk tomato plant (Physalis ixocarpa Brot.). II. Reproductive parts - Francisco C. Escobar; Leszek S. Jankiewicz; Victor M. Orduña; Juan M. Brito (Acta Societatis Botanicorum Poloniae, 2014)
The development of the reproductive parts of husk tomato plants cv. 'Rendidora' was investigated and is presented in the form of curves based on regression equations or on the average data. The number of flower buds and flowers existing on a plant was highest at the 9th week after emergence (AE) and showed a second, lower pick toward the end of the experiment. These last flower buds and flowers did not have the opportunity to produce fruits of commercial size. The number of fruits reached its maximum at the 11th week AE but a great proportion of fruits smaller than 2 cm were shed. The plants with the prostrated type of growth showed the maximum yield earlier and tended to produce a larger yield than the erect ones.